Strategi Customer Relationship Management untuk Meningkatkan Retensi Pelanggan di Era Digital - Cindy Adeliya Samosir (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
This research aims to analyze the role of Customer Relationship Management (CRM) implementation in increasing customer loyalty in the digital era. With the rapid advancement of technology, CRM has become an essential component of an effective digital marketing strategy. This research uses a qualitative descriptive method with a case study approach involving several companies that use CRM as a strategy to maintain and increase customer loyalty. Data was collected through in-depth interviews, surveys and secondary data analysis from companies using CRM platforms. Research findings reveal that effective CRM implementation—through personalization, regular communication, and leveraging customer data—can significantly increase customer satisfaction and loyalty. Additionally, this research highlights that the use of CRM allows companies to better understand customer needs and preferences, thereby providing more customized services. As a result, implementing CRM in the digital era has proven to be an important strategy for businesses to compete in an increasingly competitive market.